Children's auditory-perceptual performance in identifying phonological contrasts among stops - Berti, Larissa Cristina [UNESP]; Falavigna, Ana Elisa [UNESP]; dos Santos, Jéssica Blanca [UNESP]; de Oliveira, Rita Aparecida [UNESP] (FapUNIFESP (SciELO), 2012)
Purpose: To verify children's auditory-perceptual performance regarding the identification of contrasts among stop; to identify which phonemes and contrasts provide greater or lesser perceptual difficulty; and to verify age-related influence in auditory-perceptual accuracy. Methods: Information regarding the auditory-perceptual performance of 59 children (30 male and 29 female) in a task of identification of occlusive consonants in Brazilian Portuguese were selected from a database. The task consisted on the presentation of acoustic stimuli by headphones, and the choice of the picture corresponding to the word presented between two pictures displayed on the computer screen. The time of stimulus presentation and the reaction time were automatically computed by the PERCEVAL software. Results: It was found an 85% auditory-perceptual accuracy and a positive correlation with age. The reaction time for errors was significantly higher than the reaction time for correct responses. According to the confusion matrix, perceptual difficulty of contrasts varied: voicing cues are more salient than articulation cues. For the variable place of articulation of occlusive consonants, it was observed an auditory-perceptual asymmetry, in which the phonetic distance plays a key role in perceptual salience. Conclusion: The auditory-perceptual ability regarding the identification of stop contrasts is still not stabilized in the age range studied. The auditory-perceptual mastery of occlusive contrasts occurs gradually and, within this class, there seems to be a hierarchy in mastery.
Keywords: Auditory perception; Child; Evaluation; Phonetics; Speech